Bstan pa skyoṅ baʼi dam can chos sruṅs rnams kyi phrin las dṅos grub ʼdodʼjo : a collection of texts for the propitiation of the protective deities of Glo Smon-thaṅ in Nepal (Ngawang Topgay, 1976)
Rites for the propitiation of the local deities of Mustang (Glo Smon-thaṅ), northern Nepal.